A cultura quilombola está na escola? - Silva, Priscila Olin (2016)
Despite the recognized importance in the construction process of the history and identity of Brazil, the quilombo remnants still suffer with lack of access to rights, such as education. In the course of fighting for a contextualized education, the reference point is the National Curriculum Guidelines for Quilombola School Education, which recommend the inclusion of history and culture in quilombola education offered to students of these communities. The study aimed to investigate how the quilombola issue has been addressed in educational and political project of a school that attends students from a remnant quilombo community in Goiás. This is an exploratory and strategic social research with a qualitative approach to information. Semi-structured interviews, conversation wheel, observation of daily activities and analysis of the educational and political school project were conducted. The leadership of quilombola community, school staff and county nutritionist composed the study population.The investigation included aspects related to the general characterization of the school, the school feeding, as well as insertion of quilombola theme at school. The information was analysed in the light of the content analysis in the thematic mode. The municipality has a rural school that attends students from the quilombo. Although not in the community territory, is registered as quilombola school in the School Census, receiving different financial resources to school feeding. Three thematic categories were built: School and food; Quilombola community culture and Quilombola school education. School feeding does not meet the recommended by law and the quilombo food culture is not inserted in school activities. The lack of teacher training and the lack of teaching materials were cited as difficulties to work the quilombola subject in school. The educational and political project does not include everyday aspects of the quilombolastudents‟reality and there is a weak interaction between the school, community, municipal management of education and nutritionist. It is suggested greater coordination of these actors, so that the school's pedagogical proposal has tune with the reality of students, translating into a strengthening of quilombola culture and responding to recommended by law and demands of the community